DARI BIROKRASI KE BIROKRASI INOVATIF: PERAN TRANSFORMASI BUDAYA INSTITUSIONAL - Jabar, Syabran; Frinaldi, Aldri (SOCIAL : Jurnal Inovasi Pendidikan IPS, 2025)
Public bureaucracy in Indonesia faces significant challenges in responding to dynamic social changes and increasingly complex service demands. Despite numerous reform initiatives, a considerable gap remains between the ideal innovative bureaucracy and the actual bureaucracy, which tends to be rigid and less adaptive. This study focuses on the role of institutional cultural transformation as a key factor in realizing an innovative bureaucracy. A qualitative method was employed using a case study approach on several government agencies undergoing organizational culture change. Data were collected through in-depth interviews, participatory observations, and documentation, then thematically analyzed to identify patterns and driving factors of cultural transformation. The findings indicate that cultural transformation emphasizing values such as collaboration, creativity, and openness can shift bureaucratic work patterns towards being more responsive and innovative. Transformational leadership and reward systems supporting innovation are crucial factors in the success of cultural change. The study concludes that institutional cultural transformation is the fundamental foundation for sustaining bureaucratic innovation and comprehensive public sector reform. These findings offer important implications for policymakers and bureaucratic practitioners in designing reform strategies oriented toward human resource development and organizational values. This study also opens opportunities for further research on integrating innovative culture into public management. ABSTRAKBirokrasi publik di Indonesia menghadapi tantangan besar dalam menghadapi dinamika sosial dan tuntutan pelayanan yang semakin kompleks. Meskipun telah banyak inisiatif reformasi, masih terdapat kesenjangan signifikan antara birokrasi ideal yang inovatif dan birokrasi nyata yang cenderung kaku dan kurang adaptif. Penelitian ini fokus pada peran transformasi budaya institusional sebagai kunci dalam mewujudkan birokrasi inovatif. Metode kualitatif digunakan dengan pendekatan studi kasus pada beberapa instansi pemerintah yang sedang melakukan perubahan budaya organisasi. Data dikumpulkan melalui wawancara mendalam, observasi partisipatif, dan dokumentasi, kemudian dianalisis secara tematik untuk mengidentifikasi pola dan faktor pendorong transformasi budaya. Hasil penelitian menunjukkan bahwa transformasi budaya yang menekankan nilai-nilai kolaborasi, kreativitas, dan keterbukaan mampu mengubah pola kerja birokrasi menjadi lebih responsif dan inovatif. Kepemimpinan transformatif serta sistem penghargaan yang mendukung inovasi merupakan faktor pendukung utama keberhasilan perubahan budaya. Kesimpulan penelitian menegaskan bahwa perubahan budaya institusional adalah fondasi utama bagi keberlangsungan inovasi birokrasi dan reformasi sektor publik secara menyeluruh. Temuan ini memberikan implikasi penting bagi pembuat kebijakan dan praktisi birokrasi dalam merancang strategi reformasi yang lebih berorientasi pada pengembangan sumber daya manusia dan nilai-nilai organisasi. Studi ini juga membuka peluang pengembangan riset lebih lanjut mengenai integrasi budaya inovatif dalam manajemen publik.